Damage assessment & innovation of efficient retrofitting solution of RC slabs exposed to contact explosion - Ibrahim Mohamed Metwally (Revista IBRACON de Estruturas e Materiais, 2022)
abstract: Under contact explosions, the reinforced concrete structures can behave in a brittle manner with highly localized damage like concrete cratering, spalling, and reinforcement rupturing. High-speed fragmentation resulting from concrete spall may cause severe casualties and injuries. It is therefore important to restrained concrete fragments and improve collapse resistance of the slab. A new retrofitting technique is proposed in this paper which completely prevents fragmentation. To mitigate blast effects on civil structures, a new kind of concrete material named Ultra-High-Performance-Concrete (UHPC) is now widely studied and applied. UHPC material is known for its high compressive and tensile strength, large energy absorption capacity as well as good workability and anti-abrasion ability compared to normal strength concrete(NRC). All of recent experimental published work concerning blast performance of UHPC slabs under far or near explosion effect, on the other side, the contact explosion tests are relatively limited experimentally and nearly impossible because of security restrictions and costly in terms of both preparation and measurements. So, the real and accurate finite element models are needed to address this gap and understanding the real contact-explosion behavior of both NRC and UHPC slabs. The numerical analyses allow gaining insight into the complex failure mechanisms occurring in the slab and not directly observable. In this study, coupled smoothed particle hydrodynamics (SPH) method and finite element method is utilized to simulate the contact blast tests. Numerical results are compared with the experimental observations, and the feasibility and accuracy of the numerical model are validated. The validated numerical model provided a useful tool for designing potential blast-retrofitting solutions which can prevent the local material damage and fragmentations in both NRC & UHPC slabs subjected to contact explosion. This study introduced adequate and very efficient protection solution for both NRC & UHPC slabs exposed to contact explosion (1 kg of TNT) by utilizing the composite action generated between slabs & bonded steel plates. The 2 mm and 1 mm bonded steel plates at both faces of the NRC and UHPC slabs respectively attained a superior resistance to contact explosion.